The Effect of Firm Size, Gender, and Household Interference on MSEs Performance and Household Welfare in Indonesia - Wessti Rahmiattul (Financial Management Studies, 2024)
This study aims to analyze the effect of business size, gender, and household interference on MSE performance and household welfare in Indonesia using raw data from the 2014 Indonesian Family Life Survey (IFLS-5), with a sample of 4,314 households running non-agricultural MSEs with their own capital. Given the heterogeneous characteristics of the data and the presence of outliers, this study uses the quantile regression method with confidence level (∝=0.05). The analysis shows that business size has a positive and significant effect on MSE performance. In contrast, gender and household interference have a negative and significant effect on MSE performance. Firm size has a positive effect on household welfare. Gender has a positive effect on household welfare, but is significant only at Q0.50. And household interference has a positive effect on household welfare, but is significant only at Q0.75.